Implementasi Perlindungan Hukum Terhadap Jaminan Sosial dan Pemutusan Hubungan Kerja antara Perusahaan dengan Awak Kapal pada Perusahaan Pelayaran di Indonesia - Veby Senopati Silam; Wiwik Sri Widiarty; Gindo EL.Tobing (Syntax Idea)
Indonesia has a large and rapidly growing maritime industry, with numerous shipping companies operating vessels for various purposes, including cargo and passenger transportation. Most of these vessels are managed by hardworking and high-risk crew members. Legal protection regarding social security benefits and employment termination for maritime crew in Indonesia is a crucial issue that demands serious attention. This research aims to analyze and document the implementation of legal protection for social security benefits and employment termination between shipping companies and crew members in Indonesia. The research is conducted by examining various legal sources and real-life cases within the maritime industry in Indonesia. This study discusses the legal framework governing the rights of crew members and the obligations of shipping companies in providing social security benefits, as well as the procedures for employment termination when necessary. Additionally, this article also highlights the challenges and issues frequently faced by crew members in attaining their rights, such as discrimination, unlawful termination, and gaps in social protection. In this research, the impact of legal regulations on the practices of shipping companies and the protection of crew members' rights will be considered. This research will also evaluate the effectiveness of oversight and law enforcement by authorities in safeguarding crew members' rights. The research results indicate the need for improvements in the implementation of legal protection for social security benefits and employment termination in the maritime sector in Indonesia. This article contributes to a better understanding of legal issues related to the rights of crew members and advocates for improvements in the regulation and practices of the maritime industry.